Comparison of structural outcome between intravitreal bevacizumab and laser treatment for type 1 retinopathy of prematurity after long-term follow-up - ChenYen-Yi; ChenYun-Ju; HsuYung-Ray; ChenFang-Ting; WangJia-Kang (眼科学报; 卷 31, 编号 2 (June 2016): 《眼科学报》, 2016)
Background: To compare the structural outcome of intravitreal bevacizumab (IVB) and laser treatment for type 1 retinopathy of prematurity (ROP). Methods: This is a retrospective comparative study. From December 2002 to April 2009, patients with type 1 ROP according to criteria of Early Treatment of Retinopathy of Prematurity (ETROP) study were treated by peripheral retinal diode laser photocoagulation in nearly confluent pattern. From May 2009 to January 2015, we performed IVB for patients with type 1 ROP. The patients were closely followed until disappearance of retinal neovascularization in the laser group and regression of avascular zone in the bevacizumab group. The demographical data, postmenstrual age (PMA) for treatment, and fundus findings were recorded by chart review. The difference between laser and bevacizumab groups was compared by Student t-test and Fisher exact test. Results: We collected 43 patients (86 eyes) with type 1 ROP, including 30 male and 13 female infants. Their mean gestation age and birth body weight (BBW) were 27.5 weeks and 1,034 gm. Zone I and zone II disease were found in 8 and 35 patients. The mean PMA for treatment was 37.3 weeks. The mean follow-up period was 54.4 months. Laser treatment was administered in 26 patients, and bevacizumab injection for 17 infants. Single session of laser was performed in all patients of laser group without recurrence of retinal neovascularization. Complete regression of ROP was found in 15 infants of bevacizumab group following the first IVB. Four eyes in two patients (2/17, 11.7%) had recurrence of ROP and received additional injections and adjuvant laser treatment. There was no unfavorable anatomical results such as retinal detachment or macular ectopia or complications such as cataract or endophthalmitis in either bevacizumab or laser management. Conclusions: Laser therapy and IVB were both effective treatments for type 1 ROP to cause favorable anatomical outcomes. Single session of laser ablation in nearly confluent pattern was sufficient for complete regression of ROP in laser group. Single IVB was appropriate for managing most of cases with ROP in bevacizumab group, but a small proportion (nearly one tenth) of them had recurrent episodes requiring adjuvant therapies.